Spatio-Temporal Distribution of Aedes aegypti (Diptera: Culicidae) Mitochondrial Lineages in Cities with Distinct Dengue Incidence Rates Suggests Complex Population Dynamics of the Dengue Vector in Colombia (2023)
Aedes aegypti is the primary vector of the four serotypes of dengue virus (DENV1-4), Chi- kungunya and yellow fever virus to humans